Case report: Ectopic pregnancy in the interstitial part of the fallopian tube - Bužinskienė, Diana; Mačionytė, Monika; Dasevičius, Darius; Šilkūnas, Mindaugas (Frontiers in Surgery, 2023)
Ectopic pregnancy remains one of the most common causes of pregnancy-related death in the first trimester. 2.4% of ectopic pregnancies occur in the interstitial part of the fallopian tube. As the symptoms of this condition are non-specific and the localization is associated with a higher risk of bleeding, early diagnosis of interstitial pregnancies is important, based not only on clinical symptoms, but also on additional diagnostic methods. Early diagnosis leads to better treatment-related outcomes. We report a 32-year-old female patient who came to the emergency department because of pain in the lower abdomen and right iliac region and bloody vaginal discharge. During palpation of the abdomen, the pain was localized in the lower part of the abdomen. Human chorionic gonadotropin (hCG) was significantly increased in biochemical tests. Transvaginal ultrasound examination of internal genital organs, abdominal and pelvic computer tomography (CT) were per-formed. An ectopic pregnancy was suspected. Thus, the patient was hospitalized in the gynecology department for surgical treatment. A laparoscopy was performed and an ectopic pregnancy was diagnosed in the interstitial part of the right fallopian tube and in the right uterine corner, which led to right salpingectomy and right uterine angle resection. Thus, interstitial pregnancy is a rare and life-threatening gynecological condition due to the higher risk of bleeding compared to other ectopic pregnancies. However, appropriate diagnosis based on clinical signs, transvaginal ultrasound findings and hCG levels in the blood ensures early diagnosis of interstitial pregnancy, which leads to the choice of medical treatment with methotrexate or minimally invasive surgical techniques.